Road Safety Concerns in Nigeria: Evidence on Mechanisms and Demographic Correlates of Mild Traumatic Brain Injury from a Tertiary Trauma Centre - Selekeowei Peter Kespi Kpuduwei (Public Health, 2026)
Background: Mild traumatic brain injury (mTBI) constitutes the majority of traumatic brain injuries worldwide and is associated with substantial healthcare utilization. Contemporary epidemiological data from low- and middle-income countries are limited. Wherefore this study provides evidence for planning and prevention of this public health burden. Methods: A descriptive cross-sectional study was conducted among adult patients presenting with mTBI at a tertiary trauma centre in Abuja, Nigeria. Demographic characteristics and mechanisms of injury were analysed. Results: A total of 103 patients were included. Young adult males predominated, and road traffic accidents were the leading mechanism of injury. Conclusion: mTBI in Nigeria disproportionately affects economically productive males and is largely attributable to preventable road traffic injuries.